Sex Work as resistance to marginalization– Lessons from Black Feminist Theory, Disability Justice, and Black-led sex worker organizing. - Xaymaca, Zee (Disability Studies Quarterly, 2022)
This autoethnography seeks to add to the growing body of sex worker focused literature by shedding light on the intersections between race, gender, and disability status in sex workers’ experience. I examine my experiences with educational, social, and medical institutions in Germany and the US through a Black Feminist and Disability Justice frame in order to illustrate the insidious nature of racism, sexism, and ableism in the daily experiences of Black bodies with disabilities. Drawing on existing disability justice frameworks, such as Puar’s concept of debility, I connect my experience with entering and surviving in the sex trade to my ability to understand and survive society’s hostility. I examine instances from my life where the intersections I occupy have worked to both propel and restrain my ability to attain in societies that are decidedly anti-sex-work, ableist, and misguided on issues of race and sex. I highlight the lessons learned from sex work to connect these institutions to the unique set of challenges racialized sex workers with disability face both on and off the job. This paper provides observations on the ways that community mitigates these harms and forms a safe space for those living in society’s margins to reassert their agency. Finally, I propose means of incorporating the philosophies and methods of radical Black sex worker community organizing into a mainstreamed agenda for equity.